The best predictor of anxiety, stress, and depression among institutionalized elderly - Ni Putu Wulan Purnama Sari; Maria Manungkalit (Intelektual Pustaka Media Utama, 2019)
Anxiety, stress, and depression are the three most common negative emotional constructs found in the elderly. Evidences available worldwide about how psychological problem could be resulted in mental disorder, and there is significant difference in the context of living in the nursing home and in community setting. This study aimed to determine the best predictor of anxiety, stress, and depression in elderly living in the nursing home, useful for future modification and intervention development. This cross-sectional study involved 145 elderly in a private nursing home in Surabaya, Indonesia. HARS, SPST-20, and GDS were used in data collection. Linear regression and one way ANOVA tests were used in data analysis (α<0.05). Results showed that mostly in old individuals, mild anxiety and stress, and undepressed state were found. Sensory problems and concentration difficulties were the best predictor of anxiety and stress respectively, which were accounted for 61.2% and 65.6% variances of anxiety and stress in nursing home residents respectively. Spirits, life energy, happiness, and feeling wonderful to be alive could not predict depression significantly. Feeling inferior to others is the best predictor of depression, which was accounted for 25.9% variance of depression in this population. Low self-esteem leads to depression in nursing home residents.